Метод чисельного рішення задачі Стефана для багатофазної дифузійної системи з рухомими границями фаз - Нестеренко, Микола Григорович; Nesterenko, Mykola; Нестерннко, Олександр Іванович; Nesterenko, Oleksandr; Сахно, Вячеслав Миколайович; Sakhno, Viacheslav (International Scientific Unity, 2025)
Дана робота присвячена проблемі Стефана, до якої зводяться задачі теплопереносу з фазовим переходом рідина - тверде тіло і дифузійного масопереносу з фазовими перетвореннями в твердому тілі (розпад твердих розчинів, нанесення дифузійних покриттів). В роботі розглядається новий чисельний метод розрахунку задачі Стефана в багатофазних системах, який ґрунтується на неявній різницевій схемі. Цей метод використовує апроксимацію градієнта дифузанта нелінійною функцією безпосередньо біля рухомих міжфазних границь. This work is dedicated to the Stefan problem, which encompasses heat transfer problems with a liquid-solid phase transition and diffusion mass transfer with phase transformations in a solid (decomposition of solid solutions, application of diffusion coatings). The work considers a new numerical method for solving the Stefan problem in multiphase systems, based on an implicit difference scheme. This method employs an approximation of the diffusant gradient with a nonlinear function directly at the moving phase boundaries. It is necessary to develop highly versatile new generation machines that will have a variable, easily adaptable structure, as well as to promote the implementation of flexible multi-variant technological and production processes capable of optimizing operational performance in various natural and production conditions.
Method for numerical solution of the Stefan problem for a multiphase diffusion system with moving phase boundaries
Keywords: задача Стефана; Stefan problem; чисельні методи; numerical methods; межа розділу фаз; phase boundary; різницева схема; finite difference scheme; явне виділення рухомої границі; explicit isolation of a moving boundary